Perceiving at a distance: enaction, exteriority and possibility – a tribute to John Stewart. (October 2021) - Lenay, Charles
The aim of this article is to offer a new approach of perception regarding the position of a distant object. It is also a tribute to John Stewart who accompanied the first stages of this research. Having already examined the difficulties surrounding questions of the perception of exteriority within the framework of enactive approaches, we will proceed in two stages. The first stage will consist of an attempt to explain distal perception in terms of individual sensorimotor invariants. This poses the problem but fails to solve it. The second stage will propose a new pathway to account for spatial perception; a pathway that does not deny the initial intuitions of the autopoietic enactive approaches, but one which radically changes the conception of cognition by considering, from the perceptual stage, the need to take into account interindividual interactions. The protocol of an original experimental study will characterize this new approach considering the perceptual experience of objects at a distance, in exteriority, in a space of possibilities without parting from the domain of interaction. To do this, we have to work at the limits of the perceptual crossing, that is, at the moment when the perceptual reciprocity between different subjects begins to disappear.